Framework to analyse the impact of horizontal collaboration in supply chain of online grocery retail business - Singhal, Varun (2017)
UK online grocery market is considered as at the pinnacle of the innovation and one of the most advanced markets in the sector. In order to remain the leader in the global market, compete local retailers, access new markets and enhance speed and efficiency of the operations, many online retailers are now looking for ways to collaborate their supply chain operations with other business enterprises. Although each retailer usually has its own objectives and personalised approach to satisfy these objectives, several studies on supply chain and logistics argues that today collaboration among these retailers is not only possible but desirable in some, if not all, supply chain operations areas such as physical distribution of items to extract economical, operational, social and environmental benefits. Even though advancements in the logistics, and conversely in physical distribution, technology were once considered as the competitive advantage in the retail business, especially in the online retail business, but evidently this advantage is often short term, as technologies and practices working well for one retailer are generally copied and uniformly adopted by other retailers as well. In such a setting, online retailers have an opportunity to collaborate horizontally in terms of their distribution capabilities by sharing their knowledge information and resources. However, despite all the benefits and increasing popularity of these collaborations, only small number of firms, in the retail sector, have truly capitalised the potential of Supply Chain collaboration. This work set out to analyse various characteristics, advantages, issues and prejudices related to the implementation of the horizontal collaboration of supply chain, especially in physical distribution operation, of online grocery retailers of UK.